Peningkatan Kompetensi Public Speaking Pokdarwis Desa Wisata Wonolopo Semarang Dalam Menunjang Konten Pemasaran Berbasis Digital - Firdaus Azwar Ersyad; Ayang Fitrianti; Sinta Pramucitra (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The implementation of this community activity aims to improve the skills and knowledge of partners in the field of communication, especially communication techniques and Public Speaking and their implementation in designing digital-based marketing content. This Community Service activity is planned to be carried out in the Wonolopo sub-district, Semarang. The service implementation team made two methods, the Theoretical Method which was outlined in the form of a service module which contained 'Introductory Materials for Communication and Public Speaking and implementation in digital marketing design. The method of practice is the practice of making digital marketing content materials, until a question and answer session between the presenters and Pokdarwis members of the Wonolopo Mijen Tourism Village, Semarang City.